Kampanye Women and Children First pada Bidang Pendidikan di Tiongkok oleh United Nations of Children’s Fund (UNICEF) - Ananta, Amatya; Fasisaka, Idin; Parameswari, A.A. Agung Ayu intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRACT Education is now becoming one of the global issues that have been discussed so much. A good education will produce qualityhuman resources (HR), which will affect the welfare of the community and can support the success of a country to achieve its goals. An effort to improve the quality of education would experience a wide range of difficult problems faced, one of which is gender injusticeor gender inequality in education. This is experienced by China which is actually a country with a dense population, leading to the emergence of the problem of gender inequality in various fields, especially in education. There are several factors behind gender inequalities in education in China, among them: the first is the economic factor or poverty, the second is a preference or pattern of cultural outlook for men, the third is the policy of one-child policy issued by the Chinese government which in this case leads to violence against children and women. Based on this, in 2004, UNICEF played its role as an international organization that focuses on the well-being of children and women to help China by issuing a campaign, entitled Women and Children First. Women and Children First campaign by UNICEF aims to reduce gender inequality in various fields, including inequality in education in China. UNICEF has conducted several ways in the campaign Women and Children First, such as: installation of public service ads related to gender equality in radio, television, as well as billboards and banners and animated films on gender equality which are directly targeting individuals and society in China.Through this campaign, UNICEF provides information, understanding, values, and norms about the meaning of gender equality in China. Keywords : Gender Equality in Education, UNICEF, Women and Children First Campaign.